2019
DOI: 10.3390/su11216100
|View full text |Cite
|
Sign up to set email alerts
|

Energy Taxes, Carbon Dioxide Emissions, Energy Consumption and Economic Consequences: A Comparative Study of Nordic and G7 Countries

Abstract: Based on a panel ARDL (AutoRegressive Distributed Lag) model, this paper investigates the environmental and economic consequences of energy tax levied in the four Nordic countries and the G7 countries from 1994 to 2016. Based on the double dividend theory of environmental tax, this paper investigates five variables: energy tax, energy consumption per unit of GDP, income tax, profit tax and capital gains tax, carbon dioxide intensity and fossil fuel burning ratio. A panel ARDL model is established to empiricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…In particular, our empirical conclusions that policies relating to the carbon-tax have a positive impact on reducing CO 2 are consistent with those obtained by Lin and Li [44] for the case of Denmark, Sweden, and the Netherlands. More recently, Borozan [25] and He et al [19] also reported similar conclusions for the case of Europoen and G7 countries.…”
Section: Analysis and Findingssupporting
confidence: 58%
See 4 more Smart Citations
“…In particular, our empirical conclusions that policies relating to the carbon-tax have a positive impact on reducing CO 2 are consistent with those obtained by Lin and Li [44] for the case of Denmark, Sweden, and the Netherlands. More recently, Borozan [25] and He et al [19] also reported similar conclusions for the case of Europoen and G7 countries.…”
Section: Analysis and Findingssupporting
confidence: 58%
“…Hence, the investigation into the role of carbon-tax for countries who implemented tax and non-tax implementation countries is of logical and sound mind. As a final remark, our study joins the strand of [2,6,8,11,12,19].…”
Section: Literature Reviewmentioning
confidence: 75%
See 3 more Smart Citations